Allergic reaction to long – term Benzathine penicillin injection for secondary prevention of acute rheumatic fever and recommendations for skin testing - Regmi, PR; Upadhyaya, AB (Nepalese Heart Journal, 2013)
Background Rheumatic Fever (RF) causes 25-40% of all cardio vascular disease in developing countries. Long term benzathine penicillin injection is being used for secondary prophylaxis of RF / RHD. Although allergic reaction to penicillin is rare skin testing is performed routinely before each and every penicillin injection delivery in most of the hospitals in Nepal. Objectives Objectives of this study was to evaluate safety of long term benzathine penicillin injection and establish recommendations for penicillin skin testing. Methods Data from the registers of National RF/RHD prevention and control programme from 32 hospitals of Nepal were collected and analyzed in a retrospective study. Results 65 patients (1.4%) among 77300 injections of benzathine penicillin given to 4712 patients, had allergic reactions. 5 had anaphylaxis, an incidence of 0.1% (0.7/10000 injections), 60 had minor allergy, an incidence of 1.3%. Conclusions Life-threatening allergic reactions are very rare in patients on long-term intramuscular benzathine penicillin for secondary prevention of RF. With these rare complications, regular skin test before each and every benzathine penicillin injection delivery has no significant role. Nevertheless Skin testing is recommended before 1st injection and patients having different batch number and or brand name. DOI: http://dx.doi.org/10.3126/njh.v8i1.8331 Nepalese Heart Journal Vol.8(1) 2011 pp.16-18